Storage Studies on Commercial Salt Cured Dry Fish with Special Reference to Red Discolouration - M.M., Prasad; C.C., Panduranga Rao (Fishery Technology, 2025)
Quality of 80 samples of commercial salt cured dry fish belonging to 23 species groups were stored in polythene bags at ambient temperatures and monitored up to the point of spoilage. Red-discolouration was found to account for spoilage in 55% of the samples followed by rancidity in 38% and fungal growth in 6%. Among those showing red- discolouration 97.7% of the samples were affected within two months of storage. Fish with red-discolouration all over the surface contained very high levels of total volatile nitrogen and total red halophilic counts.